2020
DOI: 10.31940/soshum.v10i2.1316
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Perception of Online Learning during COVID-19 Pandemic: A Case Study on the English Students of STKIP Pamane Talino

Abstract: The pandemic of COVID-19 has forced the Indonesian government through its Ministry of Education and Culture to implement policies moving conventional classroom to online classroom. The current study is a collective case study consisting of analysis of survey on students' perceptions of their online learning during the pandemic. Sixty-six students of English Language Education Study Program at Pamane Talino College of Education (STKIP Pamane Talino) were involved. Their perception s of their online classroom th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
184
5
20

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 263 publications
(284 citation statements)
references
References 4 publications
(5 reference statements)
18
184
5
20
Order By: Relevance
“…They expected the facilities are available for all students both in city and village. This result is in line with the previous study conducted from Agung and OP (2020) who state that the availability of internet connection becomes one big constraint in the implementation of e-learning. In addition, respondents of this research found it essential if teachers in Indonesia are invited to join training program or workshop to support their preparation to implement e-learning.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…They expected the facilities are available for all students both in city and village. This result is in line with the previous study conducted from Agung and OP (2020) who state that the availability of internet connection becomes one big constraint in the implementation of e-learning. In addition, respondents of this research found it essential if teachers in Indonesia are invited to join training program or workshop to support their preparation to implement e-learning.…”
supporting
confidence: 92%
“…Beside the positive impacts of e-learning implementation, constraints were found in its implementation. Some constraints found are the availability of internet connection, accessibility of teaching media, and accessible learning tools (Agung & OP, 2020). The availability of internet connection in rural areas still becomes one of biggest challenges in the implementation of e-learning.…”
Section: Introductionmentioning
confidence: 99%
“…There are some previous studies related to students' perception utilizing online learning during COVID-19. According to Agung et al, (2020) indicate that accessibility is still a major factor in the success of online learning. Online learning for STKIP Pamane Talino's English Language Study Program requires more friendly platforms to increase student participation.…”
Section: B Review Of Literaturementioning
confidence: 99%
“…The government is forced to change education system rapidly to adjust the current situation i.e. changing conventional teaching and learning method to online classroom (Agung, Surtikanti, & Quinones, 2020;Al Lily et al, 2020). Not only Indonesia, many countries all over the world is insisted to provide alternative way of conducting different classroom platform because students cannot take the lesson at the institution directly (Abidah, Hidaayatullaah, Simamora, Fehabutar, & Mutakinati, 2020).…”
Section: Introductionmentioning
confidence: 99%